Knowledge, Attitude and Practices of Dental Practitioners in Chennai Towards Management of Hazardous Dental Radiological Waste –A Cross Sectional Survey - Ranjit Kumar; Uma Maheswari; Lubna Fathima; Jasmine Crena; Santo Grace; Suba.A (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Management of hazardous dental radiological waste is very important for the dentist to known and practice correct protocol. The aim of the study is to assess the knowledge, attitude and practice among the dental professionals in Chennai, towards disposal of radiographic hazardous waste.Materials and Methods: One hundred dental practitioners from different part of the city were participated in this study. A set of hundred questions were given to the education qualification divided into 2 groups, those with BDS (UG degree) and MDS (PG degree) and the answers obtained was tabulated and recorded. Descriptive statistics were calculated for all the questions recorded among the education qualification they were divided into 2 groups, those with BDS (UG degree) and MDS (PG degree) in chennai city and chi square test was done to find the association between the questions recorded. Result: Among the participants, they found a positive association between some questionnaire while assessing the experience of practice whereas based on qualification of the participant they was no association between the questionnaire. Conclusions: This study is to bring out sustainable social and behavioural change and to reinforce the moral and professional obligations of the dental surgeon towards human health and environment therefore it is important to collect base-line and follow up data to evaluate the outcome of any awareness programs aimed at promoting good hazardous waste management practice.